If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5d + 8 = 4d Reorder the terms: 8 + 5d = 4d Solving 8 + 5d = 4d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-4d' to each side of the equation. 8 + 5d + -4d = 4d + -4d Combine like terms: 5d + -4d = 1d 8 + 1d = 4d + -4d Combine like terms: 4d + -4d = 0 8 + 1d = 0 Add '-8' to each side of the equation. 8 + -8 + 1d = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 1d = 0 + -8 1d = 0 + -8 Combine like terms: 0 + -8 = -8 1d = -8 Divide each side by '1'. d = -8 Simplifying d = -8
| 9p-8=p-8 | | 3h=-2h-10 | | 16x+-15+-1=-15 | | 12x+180=-720 | | x^2+82x+81=0 | | 5logx^3=20 | | -5y+6-y=-5y-4 | | 3+9c=10c | | 4x+30=x-15 | | 3+6f=5f | | x^2+81x+81=0 | | 5b-10=10b | | -7j+10=-10-9j | | 2x+6x=-85+5 | | 2g=-16 | | -g=10g | | -10+6u=4u | | n+19=3 | | -1-3x=9x-13 | | -w+3-10w=4-10w | | -6q=-4q-10 | | 4X^1=50 | | -5s=-8s+9 | | .4x-y+6=0 | | 3n-8/2*6=6 | | 4m-8=3m | | 6+10z=-10+6z | | 4z=6z+8 | | 2j=j+9 | | X^2-6x-96=-130 | | -3f+10=-10+7f | | -3f+10=-10 |